Natural orifice transluminal endoscopic surgery in gynecology: What do we know till now? - Graziella Moufawad; Obey Albaini; Stephanie Farah; Karl Jallad (BMJ Publishing Group, 2021)
Surgical advancements are focusing currently on minimally invasive techniques, the latest of which is natural orifice transluminal endoscopic surgery. Though this approach is feasible through different natural orifices, the vaginal approach is the one which gained attention the most, given the vaginal flexibility and the ability to access pelvic and abdominal organs. Compared to gynecologists, general surgeons were precedents for using the vaginal orifice as a port of surgical entry. However, this vaginal approach is being more frequently implemented during gynecological surgeries nowadays. Advantages of natural orifice transluminal endoscopic surgery include scarless surgery, better exposure, reduced pain scores, less peri-operative complications, shorter hospital stay and improved patient satisfaction. This article provides an idea on the application of vaginal natural orifice transluminal endoscopic surgery in gynecology along with future potentials.